Faktor-faktor yang Berhubungan dengan Keluhan Kelelahan Mata pada Mahasiswa Program Studi Ilmu Kesehatan Masyarakat - Sofia Anggraini Kurmala; Willia Novita Eka Rini; Andree Aulia Rahmat; David Kusmawan; Evy Wisudariani (Lembaga Pengembangan Kinerja Dosen, 2025)
Eye strain (asthenopia) is a significant health issue among students in the Health Sciences Program at Jambi University. Most students experience symptoms such as eye pain, watery eyes, and headaches. These symptoms are often caused by excessive use of electronic devices for assignments, online lectures, and entertainment. This condition affects academic productivity and vision function. This study is a quantitative cross-sectional study. The sample size was 110 students from the Public Health Program at Jambi University, using stratified sampling. A DES-Q questionnaire was distributed to measure eye strain, and analysis was conducted using univariate and bivariate (chi-square) methods with SPSS 25. The results showed that the duration of high and moderate intensity gadget use (p-value = 0.006) and the position of gadget use (p-value = 0.029) had a significant association with complaints of eye fatigue among students. Meanwhile, viewing distance from the device (p-value = 1.000) and eye rest (p-value = 0.769) did not show a relationship. There is a relationship between the duration and position of device use and complaints of eye fatigue among students in the Public Health Program at Jambi University.